Pengaruh Inhibitor Alami Dari Biji Nangka Terhadap Laju Korosi Baja Karbon Tinggi - Andi Devi Sri Anjani; Ihsan; Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2023)
Jackfruit seed has considerable potential to be used as a corrosion inhibitor because its anti-oxidant content can inhibit the corrosion rate of the metal. This study aimed to determine the effect of variations in immersion time on the corrosion rate, the efficiency of jackfruit seed extract in inhibiting the corrosion rate, and the type of corrosion that occurs in high-carbon steel without and with inhibitors. This study used the maceration method to extract jackfruit seeds. It used the weight loss method to determine the value of the corrosion rate in the sample and used SEM testing to determine the type of corrosion that occurred in the sample. This research yielded corrosion rate values ​​in immersion without inhibitor solutions for 10 days, 20 days, and 30 days respectively, namely 263,46 mpy, 365,93 mpy, and 426,92 mpy. Whereas immersion using inhibitor solutions for 10 days, 20 days, and 30 days respectively, resulted in corrosion rate values ​​of 71,62 mpy, 53.41 mpy, and 44.95 mpy. These results resulted in inhibition efficiency values ​​of 72,81%, 85,40%, and 89,47%. The SEM test produced the type of corrosion that occurred in samples without an inhibitor solution, namely pitting corrosion. For immersion in an inhibitor solution, the type of corrosion that occurred was uniform corrosion.